Phytopharmaceutical modification of papaya (Carica papaya) seed extract on sperm quality using self-nano emulsion as contraception potential : Phytopharmaceutical of papaya seed extract self-nano emulsion as contraception - Shiyan, Shaum; Nuria , Siti Azzahra; Alzuraiqi, Lutfi Muhammad; Pratiwi, Galih; Nalindra, Wahyu Naga; Aisyah , Jasmine Rani (Pharmacon: Jurnal Farmasi Indonesia, 2024)
Carica papaya is known to reduce the quality of spermatozoa in morphology and viability of spermatozoa. Biochemical compound in Carica papaya is unstable and can easily degraded in disgetive track. Formulation of papaya seeds in the form of self-nano emulsion (SNE) is an alternative drug delivery system to increase bioavailability by lipophilic means. The sample consisted of 18 rats which were divided into 3 groups, namely the control group which was not given any treatment; the treatment group which was given papaya seed ethanol extract as much as 100 mg/kgBW and the treatment group which was given papaya seed extract-SNE as much as 100 mg/kgBW, the administration was carried out orally for 28 days. Examination of the quality of rat spermatozoa includes morphology, motility, and viability. Data analysis using One Way ANOVA and Chi-Square test. The results of the analysis showed that the decrease in morphology and viability of spermatozoa was significantly different with a result (p < 0.05) between treatment groups. As for motility, it does not have a significant difference with a result (p > 0.05) between treatment groups.. Based on the results of the study, it can be concluded that the administration of papaya seed ethanol extract and papaya seed SNE extract significantly reduces the quality of spermatozoa in the form of morphology and viability, and does not significantly reduce the motility of Wistar strain white rat spermatozoa.